Aplikasi Pencatatan Transaksi Keuangan dan Penyajian Laporan Keuangan Berbasis Web (Studi Kasus Pada CV Soetisna Putra) - Rezza Praramadhan Rahmat; Destian Arshad Darulmalshah Tamara; Endang Hatma Juniwati (Indonesian Journal of Economics and Management, 2021)
The background of this research comes from so many MSMEs in Indonesia. Not only do many MSMEs in Indonesia contribute a lot to the development of the Indonesian economy, but there are still many MSMEs that do not yet have an awareness of the importance of good financial recording and reporting. It is not uncommon for MSMEs to not know how to make financial reports or have difficulty making financial reports because employees are busy serving customers. There must be a system that can record accurately and efficiently in order to help MSMEs make financial reports. This study aims to create a transaction recording application & presentation of financial statements and try it at the company CV. Soetisna Putra.